Monumental protection activities in the context of deokupation of Crimea and parts of Donbass - Hrubinko, Andrii; DIdushin, Vasilina (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article considers the problem of legal support of monument protection activities in the context of deoccupation of Crimea and part of Donbass. Cultural heritage is the totality of all material and spiritual cultural achievements of society. Preservation of cultural heritage is an important area of humanitarian policy of the state. As a result, it is noted that the regulatory and legal support of the state management of cultural heritage protection acts as the main tool that regulates the protection of monuments. At the same time, the search for ways to optimize and streamline the legal provision of state regulatory influence in the field of cultural heritage protection requires new approaches to bridging the gaps in current legislation. With this in mind, it is necessary to develop and adopt appropriate concepts and programs, to clarify the tasks and functions of the subjects of monument protection, to regulate public and charitable activities at the legislative level, to analyze and harmonize current legislation with modern international approaches.